2014
DOI: 10.46867/ijcp.2014.27.02.08
|View full text |Cite
|
Sign up to set email alerts
|

How Molecular, Molar, and Unified Analyses Change the Meaning ofBehavioral Variability

Abstract: What effects reinforcement is assumed to have and what data are collected depend on what behavioral variability means. It has extremely different meanings in molecular, molar, and unified behavior analyses. In molecular analyses the term relates reinforcement and moment-to-moment behaving of an individual organism, as when hand shaping creates new complex paterns extended in time or as when cumulative records show complex patterns. Molecular behavioral variability is easy to see, as in these two examples, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Although most direct tests of these two sorts of theory have tended to favor the molecular view (see Cole, 1999; Peele et al, 1984; Reed, Soh, Hildebrandt, DeJongh, & Shek, 2000; Tanno & Sakagami, 2008), there are some suggestions that molar control can be seen under some conditions, especially when rates of reinforcement (see Baum, 1993; Cole, 1994), or rates of response (McDowell & Wixted, 1986; Reed, 2007a), are high. Given this, several theorists have suggested that these two views should not be seen as mutually exclusive (see Cole, 1994; Reed, 2007a; Shimp, 2014; Tanno et al, 2010), and an important line of investigation is to determine when these aspects of free-operant contingencies exert prime influence over behavior.…”
mentioning
confidence: 99%
“…Although most direct tests of these two sorts of theory have tended to favor the molecular view (see Cole, 1999; Peele et al, 1984; Reed, Soh, Hildebrandt, DeJongh, & Shek, 2000; Tanno & Sakagami, 2008), there are some suggestions that molar control can be seen under some conditions, especially when rates of reinforcement (see Baum, 1993; Cole, 1994), or rates of response (McDowell & Wixted, 1986; Reed, 2007a), are high. Given this, several theorists have suggested that these two views should not be seen as mutually exclusive (see Cole, 1994; Reed, 2007a; Shimp, 2014; Tanno et al, 2010), and an important line of investigation is to determine when these aspects of free-operant contingencies exert prime influence over behavior.…”
mentioning
confidence: 99%